METHODOLOGY FOR WORKING WITH A FABLE TEXT IN PRIMARY EDUCATION READING LITERACY LESSONS - Gulomova, Khalida (SCIENCE and SOCIETY, 2026)
The article examines the methodology of working with fable texts in reading literacy lessons in primary education. The educational significance of the fable genre, methods of instilling moral concepts in students, and techniques for developing expressive reading are analyzed. Practical recommendations are provided based on fables from Uzbek literature.